2009
DOI: 10.1038/ajh.2009.54
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Inflammatory Markers Neopterin, Sialic Acid, and C-Reactive Protein in Pregnancy and Preeclampsia

Abstract: Objective To determine whether the cellular inflammatory marker of activated macrophages and monocytes, neopterin (NEO) and the acute phase inflammatory markers sialic acid (SA) and C-reactive protein (CRP) are elevated in pregnancy and further elevated in the pregnancy syndrome preeclampsia. Methods Maternal plasma concentrations of NEO, SA and CRP were measured by high sensitivity ELISA or HPLC in 20 non-pregnant women, 40 women with uncomplicated pregnancies, 50 women with transient hypertension of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 35 publications
4
44
0
1
Order By: Relevance
“…We observed the systemic inflammatory response in pre-eclampsia through hs-CRP which is similar to the research reports of von Versen-Hoeynck 2009 [22], Belo 2009 [23]. The increase in plasma elastase in early onset of pre-eclampsia has been reported by Gupta 2006 [24].…”
Section: Discussionsupporting
confidence: 79%
“…We observed the systemic inflammatory response in pre-eclampsia through hs-CRP which is similar to the research reports of von Versen-Hoeynck 2009 [22], Belo 2009 [23]. The increase in plasma elastase in early onset of pre-eclampsia has been reported by Gupta 2006 [24].…”
Section: Discussionsupporting
confidence: 79%
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…50 Inflammation is increased in women with preeclampsia, with activated macrophages and monocytes being further increased. 52 Circulating levels of IL-1b and TNF-a are elevated in preeclampsia, 53 and infusion of a low dose of lipopolysaccharide in rats at 14 days gestation establishes a preeclampsia model with hypertension and albuminuria. 54 There is evidence to link inflammation with the modulation of differentiation in BeWo cells and trophoblast cells.…”
Section: Discussionmentioning
confidence: 99%